AN ANALYSIS OF A CHILD CALLED 'IT' BY DAVE PELZER FROM FAMILY SYSTEMS THEORY PERSPECTIVE - Fitriyantisyam, Hafizha (2017)
Child abuse has a major and long lasting effect on children's lives. Besides leaving horrible memories, the child abuse also affects the relationships among family members. This paper analyses a novel which consists of child abuse entitled A Child Called 'It' by Dave Pelzer. The aim of this paper is to see how the concepts of Family Systems Theory are realised in the issue of child abuse. There are three main theories used in this study: Family Systems Theory, the theory of child abuse, and literary elements. Qualitative data analysis is used in this paper with text as its main focus. The findings show that the main character gets abused physically and mentally by his mother. Based on Family Systems Theory, there are four concepts found in the issue of child abuse. Two concepts, which are family projection process and nuclear family emotional process, are the triggers of child abuse. Two other concepts of Family Systems Theory, which are triangling and differentiation of self, are the factors that perpetuate child abuse. Thus, this paper concludes that the concepts of Family Systems Theory are realised in four ways: family projection process, nuclear family emotional process, triangling, and differentiation of self.----------Kekerasan pada anak memiliki pengaruh yang besar dan lama dalam kehidupan anak-anak. Selain meninggalkan kenangan yang mengerikan, kekerasan pada anak juga berimbas pada hubungan antar anggota keluarga. Penelitian ini menganalisa sebuah novel tentang kekerasan pada anak yang berjudul A Child Called 'It' oleh Dave Pelzer. Tujuan penelitian ini adalah untuk melihat bagaimana konsep dalam Teori Sistem Keluarga diterapkan dalam isu kekerasan pada anak. Ada tiga teori utama yang digunakan dalam penelitian ini: Teori Sistem Keluarga, teori kekerasan pada anak, dan elemen-elemen literatur. Analisa data kualitatif digunakan dalam penelitian ini dengan teks sebagai fokus utamanya. Hasil penelitian menunjukkan bahwa pemeran utama novel ini disiksa secara fisik dan mental oleh ibunya. Menurut Teori Sistem Keluarga, ada empat konsep yang ditemukan dalam isu kekerasan pada anak di novel ini. Dua konsep, yaitu family projection process dan nuclear family emotional process, adalah pemicu kekerasan pada anak. Dua konsep lainnya, yaitu triangling dan differentiation of self, adalah faktor-faktor yang memperparah kekerasan pada anak. Jadi, penelitian ini menyimpulkan bahwa Teori Sistem Keluarga diterapkan dalam empat cara: family projection process, nuclear family emotional process, triangling, and differentiation of self.